2007
DOI: 10.1007/s00415-007-0558-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in brain reserve

Abstract: These data suggest that the same clinical severity of dementia is associated with greater reductions in cerebral metabolism in men than in women suggesting a greater degree of brain reserve in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
27
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 31 publications
9
27
0
1
Order By: Relevance
“…This difference is consistent with other reports of a sex difference in brain reserve and clinical manifestations of AD pathologic changes, 19–21 although this association remains a point of discussion. Importantly our results also showed that both smoking and increased BMI, already know to be associated with increased free radical injury in peripheral organs, 22,23 were also associated with increased CSF F 2 -isoprostanes.…”
Section: Discussionsupporting
confidence: 92%
“…This difference is consistent with other reports of a sex difference in brain reserve and clinical manifestations of AD pathologic changes, 19–21 although this association remains a point of discussion. Importantly our results also showed that both smoking and increased BMI, already know to be associated with increased free radical injury in peripheral organs, 22,23 were also associated with increased CSF F 2 -isoprostanes.…”
Section: Discussionsupporting
confidence: 92%
“…Men might be more resistant to brain pathology because they have more cognitive reserve than women. In a recent PET study, males with dementia had a greater reduction in cerebral metabolism than would be predicted based on their higher clinical function (Perneczky, Drzezga, Diehl-Schmid, Li, & Kurz, 2007). Barnes and colleagues (2005) also report that dementia pathology is more likely to be clinically expressed in women than men.…”
Section: Discussionmentioning
confidence: 99%
“…This interesting and novel finding implies that L-CR with occupation as a proxy may be more important for women in the context of larger baseline ventricular size. Previous work examining neuropathological changes in men and women has shown similar levels of AD- and FTD-related dementia severity, despite men having significantly reduced cerebral metabolic glucose rate (an indication of greater CR) [16, 85]. Future studies may benefit from examining sex differences when studying the influence of neuroimaging biomarkers on dementia severity as moderated by dynamic CR networks.…”
Section: Discussionmentioning
confidence: 95%